Impact of host age and parity on susceptibility to severe urinary tract infection in a murine model - Kline, Kimberly A. (2014)
The epidemiology and bacteriology of urinary tract infection (UTI) varies across the human lifespan, but the reasons for these differences are poorly understood. Using established monomicrobial and polymicrobial murine UTI models caused by uropathogenic Escherichia coli (UPEC) and/or Group B Streptococcus (GBS), we demonstrate age and parity as inter-related factors contributing to UTI susceptibility. Young nulliparous animals exhibited 10–100-fold higher bacterial titers compared to older animals. In contrast, multiparity was associated with more severe acute cystitis in older animals compared to age-matched nulliparous controls, particularly in the context of polymicrobial infection where UPEC titers were ~1000-fold higher in the multiparous compared to the nulliparous host. Multiparity was also associated with significantly increased risk of chronic high titer UPEC cystitis and ascending pyelonephritis. Further evidence is provided that the increased UPEC load in multiparous animals required TLR4-signaling. Together, these data strongly suggest that the experience of childbearing fundamentally and permanently changes the urinary tract and its response to pathogens in a manner that increases susceptibility to severe UTI. Moreover, this murine model provides a system for dissecting these and other lifespan-associated risk factors contributing to severe UTI in at-risk groups.